THE USE OF ‘A STOP MOTION ANIMATION VIDEO’ TO TEACH SPEAKING OF A DESCRIPTIVE TEXT TO THE TENTH GRADERS (RETAIN, 2016)
THE USE OF ‘A STOP MOTION ANIMATION VIDEO’ TO TEACH SPEAKING OF A DESCRIPTIVE TEXT TO THE TENTH GRADERS Ima Maslicha English Education Department, Language and Art Faculty, Surabaya State University. imamaslicha@mhs.unesa.ac.id Abstract Students are called successful English learner when they are able to communicate in English. In the teaching learning process, the teacher should choose an interesting media to support the students in improving their speaking ability. A stop motion animation video is one of the audio visual multimedia that can be used as a medium in teaching speaking. By using it, the teacher can help the students in watch, listen, understand, and apply the use of language contextually. This research is conducted to find out whether there is a significant difference in the students’ speaking ability after being taught by using a stop motion animation video. This research uses quantitative method, the samples of which are 33 students in X TGB1 and 33 students in X TAV 3. The data of the research are the scores of the students’ speaking ability in the post-test. The result shows that the students’ speaking ability of the experimental groupis better than that of the controlled group. Moreover, there is a significant difference in all speaking components. Keywords:Speaking, A Stop Motion Animation Video, Descriptive Text Abstrak Siswadapat disebut suksessebagai pelajar bahasa Inggris ketika mereka mampu berkomunikasi dalam bahasa Inggris. Dalam proses belajar mengajar, guru harus memilih media yang menarik untuk mendukung siswa dalam meningkatkan kemampuan berbicara mereka. Video animasi stop motion adalah salah satu dari multimedia audio visual yang dapat digunakan sebagaimedia dalam mengajar berbicara.Dengan menggunakan video animasi stop motion, guru dapat membantu siswa dalam menonton, mendengarkan, memahami, dan menerapkan penggunaan bahasa kontekstual Penelitian ini dilakukan untuk mengetahui apakah ada perbedaan yang signifikan dalam kemampuan berbicara siswa setelah diajarkan dengan menggunakan video animasi stop motion. Penelitian ini menggunakan metode kuantitatifdan sampel dari penelitian ini adalah 33 siswa di X TGB 1 dan 33 siswa di X TAV 3.Data dari penelitian ini adalah nilai dari kemampuan berbicara siswa dalam post-test. Berdasarkan hasil pengamatan, kemampuan berbicara siswa dari kelompok eksperimen lebih baik daripada kelompok kontrol. Selain itu, ada perbedaan yang signifikan untuk semua komponen dalam berbicara. Kata Kunci: Berbicara, Video Animasi Stop Motion, TeksDeskriptif.